2013
DOI: 10.1160/th13-01-0054
|View full text |Cite
|
Sign up to set email alerts
|

Does chronic kidney disease improve the predictive value of the CHADS2 and CHA2DS2-VASc stroke stratification risk scores for atrial fibrillation?

Abstract: Chronic Kidney Disease (CKD) constitutes an adverse risk factor in chronic anticoagulated atrial fibrillation (AF) patients, being related to adverse cardiovascular events, mortality and major bleeds. It is unclear if CKD adds independent prognostic information to stroke risk stratification schemes, as the risk factor components of the CHADS2 and CHA2DS2-VASc scores are themselves related to renal dysfunction. The aim of our study was to determine if CKD independently improves the predictive value of the CHADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 29 publications
(24 reference statements)
4
48
1
2
Order By: Relevance
“…2,5,10,12,13,15,17,18,20,21 Different equations were used for estimating the eGFR and classifying patients as having CKD: Cockcroft-Gault formula was used in 5 studies 15,18,20,21,25 collaboration and cystatin C clearance were also used for assessing the safety and efficacy of apixaban and dabigatran at different levels of eGFR. The remaining selected studies for the systematic review did not use any of these, because the diagnosis of CKD was retrieved from codification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5,10,12,13,15,17,18,20,21 Different equations were used for estimating the eGFR and classifying patients as having CKD: Cockcroft-Gault formula was used in 5 studies 15,18,20,21,25 collaboration and cystatin C clearance were also used for assessing the safety and efficacy of apixaban and dabigatran at different levels of eGFR. The remaining selected studies for the systematic review did not use any of these, because the diagnosis of CKD was retrieved from codification.…”
Section: Resultsmentioning
confidence: 99%
“…10 In addition, Banerjee et al found that renal impairment and/or eGFR (codified as 3 different categories: <30, 30 to 59, and 60 ml/min) did not increase the risk of ischemic stroke or systemic thromboembolism after adjustment for the CHADS 2 risk factors. Thus, if added to CHADS 2 or CHA 2 DS 2 -VASc risk scores, eGFR did not independently add to the predictive value of any of these.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,[28][29][30][31] Fourteen studies reported the incidence of a composite outcome (ischemic stroke or systematic embolism) as an outcome of interest and 4 studies only reported the incidence of ischemic stroke. Fourteen studies (77.8%) provided ≥1 adjusted risk estimate, and 11 (78.6%) of them reported an adjusted estimate for CHADS 2 : congestive heart failure, hypertension, age, diabetes mellitus, stroke/transient ischemic attack.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…6 Also, other "real world" studies have shown that adding extra points for "renal impairment" (as with the R2CHADS2 score) did not improve the predictive value of CHA2DS2-VASc. 7- 9 Nonetheless, various attempts to improve prediction of "highrisk" AF subjects using biomarkers have been proposed, but the (very) marginal improvements in c-statistics over clinical-based scores were at the cost of substantially much lower simplicity and applicability for everyday clinical practice.…”
mentioning
confidence: 99%